2018
DOI: 10.13189/ujer.2018.060107
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Personal Values in Social Entrepreneurship

Abstract: The purpose of this research is to examine to what extent pre-service teachers' personal values predict their social entrepreneurship characteristics. In this context, statistical analysis was conducted on the data obtained from 393 pre-service teachers studying at the Faculty of Muallim Rıfat Education at Kilis 7 Aralık University in 2016-2017 academic semester. The data was collected through social entrepreneurship and personal value scales. The results of the data analysis indicated the mean scores for pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Values are described as radial and sustainable standards (Schwartz, 1992(Schwartz, , 1994 where entrepreneurs can reflect on the desirability and importance of their actions. In this sense, values can guide social entrepreneurs to recognize and pursue opportunities that are not merely economic or beneficial to their business, but also to others (Akar & Dogan, 2018). Schwartz (1992) theory of values has been widely used and affirmed intercultural stability in more than 60 nations (Tartakovsky & Schwartz, 2001).…”
Section: Outcome Expectationsmentioning
confidence: 99%
“…Values are described as radial and sustainable standards (Schwartz, 1992(Schwartz, , 1994 where entrepreneurs can reflect on the desirability and importance of their actions. In this sense, values can guide social entrepreneurs to recognize and pursue opportunities that are not merely economic or beneficial to their business, but also to others (Akar & Dogan, 2018). Schwartz (1992) theory of values has been widely used and affirmed intercultural stability in more than 60 nations (Tartakovsky & Schwartz, 2001).…”
Section: Outcome Expectationsmentioning
confidence: 99%
“…It provides a strong indication that self-control is inversely related to academic procrastination [54] [55] [56]. Moreover, there is a moderate positive relationship between religious values, social skills, honesty and self-control [57].…”
Section: Resultsmentioning
confidence: 99%
“…Personal values affect the coordination and complementarity between economic and social values that often conflict [44]. The activation of individuals to think and take action is influenced by personal values, and individual activities are guided by conscious thoughts and intentions [45]. Some studies have shown a significant positive relationship between personal values, emotional and organizational commitment [46,47], and job satisfaction [48].…”
Section: Figure 1 Hypothetical Structural Modelmentioning
confidence: 99%